Epoxy metabolites of linoleic acid promote the development of breast cancer via orchestrating PLEC/NFκB1/CXCL9-mediated tumor growth and metastasis - Kai-Di Ni; Xian Fu; Ying Luo; Xin He; Hou-Hua Yin; Dong-Ping Mo; Jing-Xian Wu; Ming-Jun Wu; Xiao Zheng; Ya-Nan Liu; Qing Jiang; Ling-Tong Zhang; et al. (Cell Death and Disease)
Abstract Breast cancer (BC) is a common malignant tumor in women and requires a comprehensive understanding of its pathogenesis for the development of new therapeutic strategies. Polyunsaturated fatty acids (PUFAs) metabolism-driven inflammation is a causative factor in cancer development. However, the function of PUFAs′ metabolism in BC remains largely unknown. Here we report the role and underlying mechanism of epoxyoctadecenoic acids (EpOMEs), the metabolites of linoleic acid mediated by cytochrome P450 (CYP) monooxygenases, in promoting the development of BC, particularly triple-negative BC (TNBC). A metabolomics study identified that EpOMEs were significantly increased in the plasma of BC patients and MMTV-PyMT mice, which accounted for the upregulation of CYP2J2 in BC tumor tissues and tumor cells. Decreased EpOMEs by treatment of CYP monooxygenase inhibitors significantly alleviated tumor development in MMTV-PyMT mice. Treatment with EpOMEs and overexpression of CYP2J2 to increase EpOMEs in TNBC cells significantly promoted cellular proliferation, migration, tumor growth, and metastasis. Whereas knockdown of CYP2J2 to decrease EpOMEs inhibited tumorigenesis and lung metastasis of TNBC, which was reversed by EpOME administration. Transcriptomics and proteomics analyses revealed CXCL9 and PLEC were critical for EpOME-mediated promotion of TNBC. Knockdown of CXCL9 and PLEC inhibited TNBC progression and EpOME-mediated promotion of TNBC. Both overexpression of CYP2J2 and EpOME treatment upregulate PLEC, while PLEC upregulates NFκB1, which is a transcription regulator of CXCL9. This study extends the understanding of the function of PUFAs metabolism in BC development, providing potential therapeutic targets and dietary guidelines for patients with TNBC and other BCs. The illustration of the hypothetical mechanism CYP2J2/EpOMEs promotes the tumorigenesis and metastasis of TNBC via PLEC/NFKB1/CXCL9 signaling pathway.